A Meticulous Study Between Sira, Dhamani And Srotas - Jain, Saurabh; Kumar, Sunil; Sharma, Rashi (International Research Journal of Ayurveda & Yoga, 2021)
Acharya Charaka has defined Srotas as ‘Sravanat srotamsi’ meaning the structure through which the sravanam takes place because of transudation some of them are called ‘Srotas’. Dhamani as Dhamnat Dhamanya meaning because of pulsation, some of them are called ‘Dhamani’, and Sira as ‘Sarnat Sira’ i.e. because of the action of simply carrying a substance effortlessly from one place to another, some others are called ‘Sira’ In physiological view, Srotas is very broad term which starts from external orifices (Navsrotansi) to the very minute invisible ionic channel/gate etc. (Dosha Dhatu in Parmanu Swaroop as Dosha-Dhatuvaha Srotas). This Srotas is included the term Sira which is characterized with the flow of blood (RasaRakta with Dosha Dhatu) due to the life giving and Ranjan of Rasa so whole fluid comes under the term Rakta which expel out in Raktamokshana Karma. Sira includes the term Dhamani in which has blood but with pressure flow exerted by the contraction of heart. Acharya Charaka and Vagbhatta has this opinion as Charaka mentioned Sira Dhamani Srotas are synonyms and Vagbhatta mentioned Sira Dhamani are the Srotas only. In anatomical view, Srotas is that structure excluding the Sira entity means present in pure form i.e. without blood cells (Rakta Dhatu). Srotas is intra as well as extracellular spaces (Sravanat srotamsi). Sushruta has the same opinion as he mentioned for Srotas Sira-Dhamani vivarjitam. Sira is the structure excluding Dhamani i.e. without much pressure (Sarnat Sira). So Sushruta broadly describe about Sira and Siravyadhvidhi in separate chapters. Rest part is the structure called Dhamani having a pressure exerted by heart contraction (Dhamanat Dhamani). It is pushing mechanism to Sira to supply nutrition for functioning actions (cry, sleep, wake etc.) of the body.